Implementation of Reading Guide Strategy in Global Climate Change Material for Enhancement of Student Learning Outcome - Arozaq, Miftahul; Aman, Aman; Sunarhadi, M. Amin (International Journal of Active Learning, 2017)
The hierarchy of climate change learning concepts needs to be studied in schools. In the last four to five years, the issue of climate change has gained wider attention in the development of long-term government policy and programming so that it is necessary to integrate programs and action into learning materials in schools to mitigate the impact Global climate change. One of the learning strategies for integrating climate change into school materials through a reading guide. Reading guide is part of the application of active learning approach emphasizes the participation of higher learners so as to create a conducive learning atmosphere. Reading Guide aims to help students be more focused and easy to understand lessons delivered by teachers. The research objectives are; 1). How to study climate change material before using learning guide reading 2). What is the result of studying climate change materials after using learning guide reading. The research method is done by comparing the learning result of the students before and after using the learning of reading guide. As a testing group are students of class X IPS 2 in SMA Al-Islam 1 Surakarta a number of 36 students. The instrument used is a test, used to determine the effectiveness of learning reading guide consisting of 25 items. The result of this research is the result of study of climate change material before using the average reading guide learning is 41,22. After studying climate change materials using learning guide guidance, there is an increase of learning result to an average of 53.11. The conclusions obtained from this study indicate that learning using the reading guide is affective